Occupational Attributes and Occupational Gender Segregation in Sweden: Does It Change Over Time? - Hustad, Ingvill Bagøien; Bandholtz, Johan; Herlitz, Agneta; Dekhtyar, Serhiy (Frontiers in Psychology, 2020)
Sweden consistently ranks at the top of international assessments of gender equality, but paradoxically exhibits marked horizontal gender segregation in the labor market. By combining administrative and respondent-collected data, this study investigates whether occupational attributes are associated with sex distribution in Swedish occupations over a ten-year period between 2002-2011. Results show that the proportion of women was higher, on average, in occupations high in people orientation and verbal demands and lower in occupations high in things orientation and numerical demands. Mixed linear models showed a trend for desegregation during this period, as the proportion of women in people-oriented occupations has declined and a trend for an increase in the proportion of women in numerically demanding occupations was observed. Occupational attributes aid the understanding of gender segregation but patterns of segregation seem to change over time.